Book Reviews. Issue 1 (1st June 2019) - Gillespie, John; Shuttleworth, Kyle; Fox, Nik Farrell; Neary, Mike
Abstract : Jean-Paul Sartre, Being and Nothingness: An Essay in Phenomenological Ontology, trans. Sarah Richmond (London: Routledge, 2018), lxvii + 848 pp., ISBN: 978-0-415-52911-2 (hardback) Jonathan Webber, Rethinking Existentialism (Oxford: Oxford University Press, 2018), 256 pp., ISBN: 978-0-198-73590-8 (hardcover) William L. Remley, Jean-Paul Sartre's Anarchist Philosophy (London: Bloomsbury Academic, 2018), vii + 277 pp., ISBN 978-1-350-04824-9 (hardback) William Rowlandson, Sartre in Cuba – Cuba in Sartre (London: Palgrave Macmillan, 2018), vi + 132 pp., ISBN 978-3-319-61695-7